Navigating change: New Professionals conference - McLachlan, Margaret (Public sector (Wellington), 2014)
About 170 new professionals gathered in Wellington for the biennial IPANZ New Professionals conference in early August. With between zero and five years' work experience, these new professionals are very much the future face of the public sector. So what could the future hold for these new professionals? IPANZ Communications Adviser Margaret McLaghlan shares messages from three presenters at the conference.